Desquamative Inflammatory Vaginitis and Plasma Cell Vulvitis Represent a Spectrum of Hemorrhagic Vestibulovaginitis. Issue 1 (January 2022) - Song, Myriarm; Day, Tania; Kliman, Len; Otton, Geoff; Yap, Desiree; Pagano, Ross; Tan, Yasmin; Scurry, James
Abstract : Objective: The aim of the study was to identify whether desquamative inflammatory vaginitis (DIV) and plasma cell vulvitis (PCV) are distinct clinicopathologic entities. Materials and Methods: The pathology database identified biopsies described as "vaginitis" or "vulvitis" occurring in nonkeratinized epithelium or mucocutaneous junction. Exclusions were age less than 18 years, unavailable slides or records, concurrent neoplasia, or histopathology consistent with other entities. Clinical data included demographics, symptoms, examination, microbiology, treatment, and response. Histopathologic review documented site, epithelial thickness and characteristics, infiltrate, and vascular abnormalities. Cases were analyzed according to histopathologic impression of DIV or PCV based on previous pathologic descriptions. Results: There were 36 specimens classified as DIV and 18 as PCV from 51 women with mean age of 51 years; 3 (6%) had concurrent biopsies with both. Pain was more common in PCV, but rates of discharge, itch, and bleeding were comparable. Rates of petechiae or erythema were similar and vaginal examination was abnormal in 72% of PCV cases. All DIV and 33% of PCV occurred in squamous mucosa; the remaining PCV cases were from mucocutaneous junction. Mean epithelial thickness, rete ridge appearance, exocytosis, and spongiosis were similar in DIV and PCV. Epithelial erosion, wide-diameter lesions, plasma cells, and stromal hemosiderin occurred in both but were more common in PCV. Lymphocyte-obscured basal layer, narrow-diameter lesions, hemorrhage, and vascular congestion were seen in both, but more common and marked in DIV. Conclusions: Desquamative inflammatory vaginitis and PCV have overlapping symptoms, signs, and histopathologic features. They may represent a single condition of hemorrhagic vestibulovaginitis with varying manifestations according to location and severity.